2002
DOI: 10.1097/00006676-200208000-00002
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Vascular Endothelial Growth Factor Predicts Early Recurrence and Poor Prognosis after Curative Resection for Ductal Adenocarcinoma of the Pancreas

Abstract: In pancreatic adenocarcinoma, the VEGF expression and the height of MVD are closely correlated, and both-rather than UICC stage and TNM classification (tumor size and nodal involvement)-are markers of prognostic relevance after curative resection. Furthermore, VEGF is a predictor of early recurrence after curative resection. The current study indicates that VEGF may promote the distribution of metastases, leading to early cancer recurrence and poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
92
2
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(106 citation statements)
references
References 32 publications
3
92
2
9
Order By: Relevance
“…VEGF is upregulated in many human tumours and its expression has usually been correlated with a high microvascular density and poor clinical outcome (Itakura et al, 1997;Seo et al, 2000;Hui et al, 2002;Niedergethmann et al, 2002). In the present study, VEGF expression detected in 78% of PETs, mainly in highly vascularised benign cases, is in accordance with previous results La Rosa et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…VEGF is upregulated in many human tumours and its expression has usually been correlated with a high microvascular density and poor clinical outcome (Itakura et al, 1997;Seo et al, 2000;Hui et al, 2002;Niedergethmann et al, 2002). In the present study, VEGF expression detected in 78% of PETs, mainly in highly vascularised benign cases, is in accordance with previous results La Rosa et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…28 The correlation between VEGFA expression and the survival remains significant even after a surgery putatively considered as curative. 39 These results are consistent with the discovery that microvessel density and vascular proliferation index were significantly associated with larger tumor size and lymph node metastasis. 40 A recent study demonstrated that focal VEGFA locus amplification is regularly detected in PDAC.…”
Section: Discussionsupporting
confidence: 90%
“…Our data did not show any correlation between the immunohistochemical expression of VEGF and tumor grade, stage or patients survival. But, such association was reported for tumors of several organs such as prostate 9 , pancreas 10 , lung 11 and colon 12 .…”
Section: Discussionmentioning
confidence: 96%